Isolation and characterization of viral nervous necrosis virus on newly established marine fish cell line and its pathogenicity in non-marine host - Hasoon, Mauida F. (2011)
In Southeast Asia, the intensification of aquaculture industry has led to the occurrence of various infectious diseases. Virus diseases in particular, affecting especially the larval and juvenile stages, are the most suppressing factors for sustainable production of high value fish species such as seabass (Lates ca/carifer). Inevitable, because of lack of sensitive methods that could be used for diagnosis and the inadequacy of pathogen control, the aquaculture industry will continue to be plagued by these diseases. Currently, viral nervous necrosis (VNN) is one of fish diseases listed by the Office International des Epizooties (OlE) as a notifiable disease in the production of marine fish worldwide. Thus the main objective of the present study was to determine the role of VNN virus (VNNv) as a pathogen in the Malaysian aquaculture industry, with emphasis on virus isolation in susceptible cell line, virus identification using polymerase chain reaction (PCR) and identification of characteristic microscopy lesions in VNNv infections. A new cell line designated as Asian Seabass Brain (ASBB-1) was derived from the brain tissue of seabass cultured in Malaysia. This cell line was maintained in Leibovitz L-15 media supplemented with 10% fetal bovine serum (FBS). The ASBB-1 cell line was sub-cultured more than 60 times over a period of 15 months. This cell line consists predominantly of fibroblastic-like cells, which are able to grow at temperatures between 20°C and 30°C with an optimum temperature of 25°C. At 25°C, the growth rate of these cells increased as the proportion of FBS increased from 5 to 20% with optimum growth at 15% or 10% FBS. The ASBB-1 cell line was characterized by karyotyping, and chromosome number distributions were different with subcultures P20 and P50 producing 48 and 46 chromosome peaks respectively. The ASBB-1 cells showed 90% viability after recovery from one year storage in liquid nitrogen. The ASBB-1 cells up on characterization by peR using primer sets of microsatellite markers of Asian seabass (Lates ca/carifer) were shown to be similar to the cells from tissues of seabass at 250 bp. The VNNv isolate derived from seabass was tested positive for VNN by the 102000 Kit®. The isolate designated UPM08-1 M was used in the cell line infectivity study. The susceptibilities of ASBB-1 cell line isolate and the highly permissive commercial SSN-1 cells to UPM08-1 M were compared. The results showed that ASBB-1 cell line was susceptible to VNNv (RGNNV genotype) with typical cytopathic effect (CPE) manifesting mainly as rounding-up at1 day post infection (dpi), severevacuolationwithin3-5dpi and complete detachment within 7dpi. The VNNv-induced CPE was further elucidated by electron microscopy (EM). Under EM, the ASBB-1cellsexhibitedvacuolated degeneration with presence of viral inclusion-like bodies. The CPE of VNNv on ASBB-1cells was producedat a virus titer of 109 . 5 TCID50/ml. This indicated that the ASBB-1 cell line is highly susceptible for use in the isolation of VNNv. Biophysical and biochemical characterization of VNNv isolate was determined by heat treatment, UV irradiationand the stability under effect of chemical disinfectants. The VNNv isolate showed susceptibility to heat treatment at 60°C within 30 minutes with no viable virus after 1 hour. UV irradiation at an intensity of 440 mWrcm2 resulted in a reduction in virus titer after 8 minutes. The virus appeared relatively resistant to changes in pH ranging between 2 to 11 after 1 hour incubation at 25°C. Treatment with 2% formalin was not totally effective even after 6 hours. Iodine did not inactivate the virus. Molecular characterization of the tissue culture-propagated virus using RT-PCR and nested peR, showed positive amplifications of genome size of 460 bp and 220 bp respectively. The 220 bp nucleotides from the T4 region of the coat protein gene was sequenced and the phylogenetic analysis resultsshowed close resemblance between the UPM08-1 M strain andSBNNV and GPNNV2strains of Malaysianisolates.The local isolate of UPM08-1 M also showed phylogenetic similarity with other strains from South East Asia, while showed relatively distant similarity with other VNNv strains from the Middle East. Cold water VNNv strains isolated from Norway, Canada and USA were distant phylogenetic relations to the UPM08-1 M strain. Experimental infectivity study was also performed using fresh water guppy fish (Poecilia reticulata) as a model. Guppies were intra nasally infected with 0.1 ml of the UPM08-1M strain at a titre of 109.5 TCID5010.1ml. Although the artificial infection resulted in slight mortality (11%) occurring within 14 days post inoculation, the VNN-specific lesions such as necrosis and vacuolation in the target organs of brain and retina were evident. The presence of virus in infected brain and retina tissues was confirmed by transmission electron microscopy (TEM). The VNNv from experimentally infected guppy was successfully reisolated in ASBB-1 cells inoculated with homogenate of brain and retinas of the survivors. There was gradual increment of virus titer in the guppy throughout the experimental period. The results indicated that guppy fish could be infected with VNNv isolated from diseased seabass. In summary, the study successfully isolated VNNv using the ASBB-1cell line. Complete CPE of this cell line was observed within 5 - 7 dpi after infection with VNNv at producing considerable higher titer of 1095TCID5010.1ml. Thus ASBB-1 cells can be recommended for VNNv (RGNNV genotype) isolation and will be an important tool for future conduct of fish health assurance programs in the aquaculture industry. The study also showed that RT-PCR followed by nested- PCR is a sensitive technique for identification of VNNv isolated from sea bass. It was also shown that guppy fish could be experimentally infected with VNNv, thus can be used as a virus-infection model.